Three domains in bloom's taxonomy - Azzahra, Khairunnisa; Arbeni, Wawan; Miranda, Miranda; Putri, Adeliya Maysaroh; Putri, Mayra Amelia (EDUCTUM: Journal Research, 2026)
Bloom's Taxonomy classifies educational objectives into three main domains: cognitive, affective, and psychomotor. The cognitive domain relates to students' intellectual abilities and thought processes, from mastery of basic knowledge to complex evaluation skills. This domain directs educators to emphasize not only memorization but also encourage in-depth understanding and the development of critical and creative thinking skills. The affective domain encompasses the feelings, attitudes, emotions, and values ??that develop within an individual. This domain plays a crucial role in creating learning that is not only cognitively effective but also contributes to the formation of students' character, attitudes, and morals. Meanwhile, the psychomotor domain focuses on physical and manipulative skills involving muscle coordination and motor skills. This domain encompasses various levels of ability, from perception, readiness, reaction, mechanisms, complex skills, adaptation, to creativity. These three domains complement each other in the learning process to develop students' competencies in a holistic and balanced manner. By understanding and integrating the three domains of Bloom's Taxonomy into learning planning and implementation, educators can create a more meaningful, comprehensive learning experience oriented toward developing students' full potential.